Burden and risk factors for road traffic injuries in two districts of Kenya: a descriptive analysis. (7th October 2012) - Bachani, AM; Herbert, HK; Mogere, S; Akungah, D; Osoro, E; Maina, W; Stevens, K; Hyder, AA
Abstract : Background: A combination of increasing vehicle volume on the road, evolving mix of vehicles, poor infrastructure, and unsafe vehicles has led to increasing road traffic crashes, injuries and fatalities in Kenya. Aims/Objectives/Purpose: This study aims to assess the current epidemiology of Road traffic injuries (RTIs) and status of risk factors. Methods: Primary and secondary data sources were used. Secondary data included a systematic literature review and an analysis of police, medical, and vital registration data. Primary data collection included observational studies, roadside knowledge, attitude and perceptions surveys, focus group discussions and household surveys. Results/Outcomes: The overall RTI rate in Kenya was 60 per 100 000 population in 2009, with vehicle passengers, and males between 15–45 years being the most affected. Injuries to motorcyclists increased at an annual rate of approximately 29% (p<0.001). Fatalities due to RTIs increased at an annual rate of 7% (p<0.001) for the period 2004–2009. Speeding was a major problem, with about half of all vehicles observed in Thika and Navasha speeding—most of these being public service vehicles. Helmets were used by less than 1/3 of motorcycle drivers and fewer than 2% passengers in both study districts. The household survey indicated that only one in five individuals own a vehicle in the two districts. The majority of the population (72%) uses public transport. Significance/Contribution to the Field: This study highlights the significant burden of RTIs in Kenya. Focusing on increasing helmet and reflective clothing use and enforcement of speed limits has the potential to prevent a large proportion of this burden.